1990
DOI: 10.2527/1990.68124167x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem interactions of muscle temperature, pH and extension on beef quality.

Abstract: The effect of pH, temperature and structural damage of muscle early postmortem on the quality of beef, particularly tenderness, was examined in a randomized complete block design with a 2 x 2 x 2 factorial. Semitendinosus muscles were excised from the right sides of 64 Charolais crossbred steer carcasses, placed in a restraint device in a controlled environment and subjected to high (31 degrees C) or low (20 degrees C) temperature, high (control) or low (electrically stimulated) pH and restraint at excised len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The significant interaction between extension and temperature for shear force indicated that muscle extension for a short period of time early postmortem affected meat tenderness. Extended muscles had lower shear forces when aged at the low temperature than when aged at the high temperature (Bruce and Ball 1990). Thus, meat tenderness of Hanwoo should be higher in 5C storage samples than 0C storage samples.…”
Section: Resultsmentioning
confidence: 99%
“…The significant interaction between extension and temperature for shear force indicated that muscle extension for a short period of time early postmortem affected meat tenderness. Extended muscles had lower shear forces when aged at the low temperature than when aged at the high temperature (Bruce and Ball 1990). Thus, meat tenderness of Hanwoo should be higher in 5C storage samples than 0C storage samples.…”
Section: Resultsmentioning
confidence: 99%
“…The negative correlation of muscle weight with L* 24h suggested that heavy muscle weights, which were associated with heavy carcass weights (Girard et al, 2011), lightened muscle colour because increased lightness is associated with increased post mortem muscle temperatures (Bruce & Ball, 1990); however, this postulation could not be examined further as pre-rigor post mortem muscle temperatures were not measured (Girard et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Only few authors give specific value of the intensity and its range (Bowles et al, 1983;Bruce & Ball, 1990;Hwang & Thompson, 2001;Solomon, 1988).…”
Section: Introductionmentioning
confidence: 97%